2019
DOI: 10.1039/c9gc02808k
|View full text |Cite
|
Sign up to set email alerts
|

Lytic polysaccharide monooxygenase (LPMO) mediated production of ultra-fine cellulose nanofibres from delignified softwood fibres

Abstract: An environmentally friendly, energy-efficient method for cellulose nanofibre (CNF) production from softwood holocellulose utilising oxidative enzymes, lytic polysaccharide monooxygenases (LPMOs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 40 publications
6
63
1
2
Order By: Relevance
“…Much research has been devoted to this new class of enzymes, especially in biomass saccharification for the production of biofuels ( Johansen, 2016 ). LPMOs may also be useful in the production of nano-cellulose ( Hu et al, 2018 ; Koskela et al, 2019 ; Valenzuela et al, 2019 ). However, few studies have been performed on fibre modification for pulp and paper applications.…”
Section: Discussionmentioning
confidence: 99%
“…Much research has been devoted to this new class of enzymes, especially in biomass saccharification for the production of biofuels ( Johansen, 2016 ). LPMOs may also be useful in the production of nano-cellulose ( Hu et al, 2018 ; Koskela et al, 2019 ; Valenzuela et al, 2019 ). However, few studies have been performed on fibre modification for pulp and paper applications.…”
Section: Discussionmentioning
confidence: 99%
“…For cellulose nanofiber production from various cellulosic fiber resources, the individualization of cellulose microfibrils is often facilitated by the enzymatic or chemical pretreatments, for example, by using the oxidative enzyme lytic polysaccharide monooxygenase, [ 15 ] TEMPO‐mediated oxidation, [ 13 ] carboxymethylation, [ 16 ] or cationization. [ 17 ] Yano et al [ 18 ] have previously employed acetylation to avoid the fibril aggregation formed through interfibril hydrogen bonds, transforming pulp fiber to nanostructured fiber.…”
Section: Figurementioning
confidence: 99%
“…A recent published study on using LPMOs to produce nanocellulose [ 208 ] clearly demonstrated that a combination of LPMOs and xylanase enzymes resulted in improved nanofibrillation of kraft pulps. Later, Koskela et al, demonstrated that CBM-free LPMOs are less focused and thus act in a more dispersed manner compared to the CBM-containing enzymes, which leads to greater fiber thinning and better surface charge dispersion [ 207 ]. The same study further showed that LPMOs containing fungal CBMs produced fragmented, soluble products, which is likely due to the binding preferences of the fungal CBM 1 (i.e., specific foci on the crystalline regions of cellulose).…”
Section: Enzymatic Processing—emerging Research Associated With Biorementioning
confidence: 99%
“…If a high yield of fermentable sugars is indeed an intended goal, it seems that LPMO-containing mixtures would benefit from cellobiohydrolases; however, such a formulation has not been reported to our knowledge. Although LPMOs combined with endoglucanase produce dispersed CNFs effectively [ 207 ], it is unlikely that these enzyme mixtures can produce CNCs in the absence of other hydrolytic agents. This is because LPMOs act primarily on the exposed surface regions of cellulose, where they leave residual surface carboxylation resulting in effective fiber dispersion.…”
Section: Enzymatic Processing—emerging Research Associated With Biorementioning
confidence: 99%